Quantitative evaluation of power transfer efficiency of UHF RFID passive systems. Issue 12 (1st June 2015) - de Souza, A.C.; Duroc, Y.; Vuong, T.P.; Luce, A.
Abstract : A procedure to evaluate the power transfer efficiency of ultra‐high‐frequency (UHF) radio‐frequency identification (RFID) passive systems is presented. The ratio between the available power at the tag antenna and the input power into the reader antenna is measured for the first time in the UHF RFID frequency band. The power absorbed by the tag antenna is measured using a transition and matching circuit.